If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3x + 1 = 4x + -3 Reorder the terms: 5 + 1 + -3x = 4x + -3 Combine like terms: 5 + 1 = 6 6 + -3x = 4x + -3 Reorder the terms: 6 + -3x = -3 + 4x Solving 6 + -3x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -3x + -4x = -3 + 4x + -4x Combine like terms: -3x + -4x = -7x 6 + -7x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -7x = -3 + 0 6 + -7x = -3 Add '-6' to each side of the equation. 6 + -6 + -7x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -7x = -3 + -6 -7x = -3 + -6 Combine like terms: -3 + -6 = -9 -7x = -9 Divide each side by '-7'. x = 1.285714286 Simplifying x = 1.285714286
| 19.5=2.26w+15.86 | | 10x+2y*2y=100 | | 2timesy=3.6 | | .5+2.5y=2.6+0.4y | | x+y-62=-27 | | 10(3x+19)=70 | | 7(3s+3)=252 | | (-5/28Z^7)(7/20z^2) | | 5x^2+3xy-2y^2=2 | | 3*y*log(y)-e^-((30/e-30*y)^4)/20 | | 11x+66y=3z | | -0.2+0.4x=-6.5+2.5x | | .36(6)+.6x=.12(36+x) | | -21=5x-10 | | 5(a-2)=85 | | -(-8x)=(-66) | | 9x-8=5+20 | | 6x+6=34-4x | | x^2=20.2 | | 6(5z+-1)+-5(z+2)=7(z+1) | | 5y-2x=13 | | 29.5+2a=9.5(3.5a-6) | | x(x-5)=x^2-11x+30 | | 6(5z-1)-5(z+2)=19(z+1) | | 8(9s+2.5)=-22.5+5.5s | | 3x-2y+52=38 | | -2y+5x=-1 | | -3(4.5+7.5v)=-23.5 | | X=83.1 | | 4k-8k=20.5 | | e^4-7x=896 | | 3-9.5(1+3.5d)=30.5 |